Evaluasi Komposisi Tubuh dan Pemanfaatan Nutrien di Ambing Kambing Peranakan Etawah Laktasi yang Diberi Pakan Fermentasi Limbah Tempe: Evaluation of Body Composition and Nutrient Uptake on the Mammary Gland of Ettawah Crossbred Goat Lactation Fed by Fermented Tempeh Waste - Dewi Apri Astuti; Erika B Laconi (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2019)
The aim of this study was to evaluate the body composition, nutrient uptake in mammary gland and milk amino acid profile of lactating Etawah Crossbred goats fed by tempeh by product. Twelve lactating goats were randomly allocated into three groups which fed by ration containing concentrate (R1), concentrate plus 25% fresh tempeh waste (R2) and concentrate plus 25% fermented tempeh waste (R3). Tempeh waste was fermented by Aspergillus niger. Kinggrass was given 50% of the total ration for all groups. Urea space technique was used to measure body composition before and after the experiment was done. Milk production was calculated two times a day during two months after giving birth (postpartum). Total milk protein and amino acid, whey and casein were analyzed by kjeldahl method and amino acid analyzer respectively. Nutrient uptake in mammary gland was calculated base on Fick principles. Result showed that there was significantly different on body weight, but on body water, protein and fat had no significant difference between the treatments. The best milk production was found in fermented tempeh waste group. Concentration of glutamic acid was dominant than other essential amino acids in whole milk and casein but there were no significant difference between groups for those essential amino acid profile. It was concluded that fermented tempeh waste could substitute 50% of total concentrate and had the highest body weight, milk yield and nutrient uptake in the mammary gland of lactating Etawah Crossbred goats. Key words: body composition, fermentation, lactating PE goat, nutrient uptake, tempeh waste DAFTAR PUSTAKA Astuti DA & Sastradipradja D. 1998. Measurement of body composition using slaughter technique and urea-space in local sheep. Indonesian Journal of Veterinary Science. 3: 1-9 Astuti DA & Sastradipradja D. 1999. Evaluation of body composition using urea dilution and slaughter technique of growing Priangan sheep. Media Veteriner. 6 (3) : 5-9. Astuti DA, Sastradipradja D & Sutardi T. 2000. Nutrient balance and glucose metabolism of female growing, late pregnant and lactating ettawah crossbred goats. Asian-Australasian Journal of Animal Sciences. 13:8: 1068-1077 Astuti DA& Wina E. 2002. Protein balance and excreation of purine derivatives in urine of lactating etawah crossbred goats fed with tempe waste. Jurnal Peternakan dan Veteriner. 7(3) : 162-166 Astuti DA, Baba AS & Wibawan IWT. 2011. Rumen fermentation, blood metabolites, and performance of sheep fed tropical browse plants. Media Peternakan. 34 (3) : 201-206 Astuti DA & Sudarman A. 2015. Status fisiologi, profil darah dan komposisi tubuh domba yang diberi minyak lemuru tersaponifikasi dan disalut dengan herbal. Buletin Peternakan. 39 (2): 116-122. Badan Pengendalian Pengendalian Dampak Lingkungan Daerah. 2000. Laporan Pertanggungjawaban Pembangunan Instalasi Pengolahan Limbah Cair Industri Tahu Tempe PRIMKOPTI Ngoto Yogyakarta. Yogyakarta (ID) : Setwilda Propinsi DIY Bishop JM, Hill, DJ, & Hosking CS. 1990. Goat milk does not suppress the immune system. Journal of Pediatrics. 116: 862-867 Bruhn JC, FST & Davis CA. 1999. Dairy goat milk composition. https://drinc.ucdavis.edu/goat-dairy-foods/dairy-goat-milk-composition Cant JP, DePeters EJ & Baldwin RL, 1993. Mammary amino acid utilization in dairy cows fed fat and its relationship to milk protein depression. Journal of Dairy Science. 76 (3) :762-774 Chaiyabutr N, Komolvanich S, Preuksagorn S & Chanpongsang S. 2000. Comparative studies on the utilization of glucose in the mammary gland of crossbred holstein cattle feeding on different types of roughage during different stages of lactation. Asian-Australasian Journal of Animal Sciences. 13 (3): 334 – 347. Laconi EB, & Jayanegara A. 2015. Improving nutritional quality of cocoa pod (theobroma cacao) through chemical and biological treatments for ruminant feeding: in vitro and in vivo evaluation. Asian-Australasian Journal of Animal Sciences Open Access. http://dx.doi.org/10.5713/ajas.13.0798. Lehninger AL. 1982. Principles of Biochemistry. New York (US): Woth Publisher, Inc. NRC. 1990. Nutrient Requirement of Goat. Washington (US): National Academy of Science. Panaretto BA & Till A.R.. 1963. Body compositition in vivo. II. The composition of mature goats and its relationship to the antypyrene, tritiated water and acetyl-4-aminoantipyrene spaces. Australian Journal of Agricultural Research. 14 (6): 926 – 943 Park YW. 1991. Goat milk as a substitute for those who are lactose intolerant. Journal of Dairy Science 74:3326-3333 Riis PM. 1983. Dynamic Biochemistry of Animal Production. New York (US): Elsevier Science Rovanis. 1995. Letters in applied microbiology. Journal of Milk and Food Technology. 20 (3): 164-167 Steel RGD & Torrie JH, 1993. Principles and Procedures of Statistics. New York (US): McGraw Hill Book Co. Inc. Shapiro BA, Harrison RA & Walton JR, 1982. Clinical Application of Blood Gas. 3rd ed. London (UK): Book Medical Publishers, Inc. Waghorn GC & Baldwin, RL. 1984. Model of metabolic flux within mammary gland of the lactating cows. Journal of Dairy Science. 67: 531-544